Analysis of the graduate and postgraduate courses demand on Feira de Santana industry - Alves, Edillane Silva (2023)
The municipality of Feira de Santana plays a pivotal role in the economic growth in the state of Bahia. According to data from the Brazilian Institute of Geography and Statistics (IBGE), the municipality has approximately 624,000 inhabitants and a Gross Domestic Product (GDP) of around 15 billion Brazilian reais annually, ranking as the 3rd largest in Bahia and the 74th in Brazil. To ensure the continuous economic growth of the municipality, there is a pressing need for a qualified workforce. Therefore, the aim of this study is to systematically examine and analyze the demand for undergraduate and postgraduate programs in the industry of Feira de Santana. The methodology employed was based on data collection, incorporating both qualitative and quantitative approaches, from industries located in Feira de Santana and the microregion within the Portal do Sertão. The project's development encompassed six stages: 1 – selection of the data collection instrument; 2 – formulation of a questionnaire with closed-ended questions; 3 – creation of an electronic questionnaire; 4 – data collection; 5 – data analysis; 6 – presentation of the study’s results at technical and scientific events. Results indicate a demand for undergraduate programs in Engineering or Management and a postgraduate program in the field of Management in the form of MBA specialization. It is noteworthy that currently, the Center for Science and Technology (CETENS) at the Federal University of Recôncavo da Bahia (UFRB) does not offer the community Management courses such as Administration, Accounting, or Economics, nor does it offer postgraduate courses in the same area. Thus, we identified two growth vectors in the project. The first is based on the ongoing expansion of Engineering/Technology courses, such as Chemical Engineering, Computer Science, Automation, and Architecture. The second vector is focused on management courses, as mentioned earlier. A study was conducted to understand the problems and difficulties encountered during the project's execution using quality tools such as Brainstorming (BS), Ishikawa, 5 Whys, 5W2H, and PDCA. A proposed solution was put forth for the continuation of activities. An analytical study was carried out, stratifying the 627 industries in Feira de Santana, and a recommendation of 27 undergraduate courses was suggested to meet this demand. Nevertheless, the results indicate the strengthening of the relationship between CETENS and the industry, a potential improvement in the future employability of CETENS graduates, and the proposal of guidelines for the development and introduction of new undergraduate and postgraduate courses at the advanced campus of CETENS/UFRB.